ANALISIS KEPUASAN PENGGUNA KERETA REL LISTRIK RUTE COMMUTER LINE BOGOR - El Fikri, Nabil; Santoso, R. Slamet (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2025)
The Jabodetabek Metropolitan Area as the largest metropolitan area in Indonesia has the highest level of commuter movement with KRL transportation mode as the main choice of commuter workers. The number of Jabodetabek KRL users continues to increase every year along with the increasing number of urban residents in Indonesia. However, the increasing number of Jabodetabek KRL users each year is not accompanied by increasing user satisfaction. The quality of service that is not in accordance with what is expected by users and the high number of KRL user complaints through social media raises a number of questions about the responsiveness of KRL service providers in handling KRL user complaints. The purpose of the study is to determine the relationship of Service Quality (X 1 ) with User Satisfaction (Y), the Relationship of Complaint Handling (X 2 ) with User Satisfaction (Y), and the Relationship of Service Quality (X 1 ) and Complaint Handling (X 2 ) with User Satisfaction (Y) simultaneously to KRL users on the Bogor Commuter Line route by applying matrix theory. The Bogor Commuter Line route is the research locus with the highest occupancy rate compared to other routes. This research applies a quantitative approach with an explanatory type through data collection in the form of questionnaires, documentation, and interviews of KRL users based on proportional random sampling techniques as many as 100 respondents scattered at each station on the Bogor Commuter Line route. The analysis techniques used are Spearman Rho validity test, Cronbach's alpha reliability test, Kendall Tau correlation (τ), Kendall Concordance (W), and Coefficient of Determination (R 2 ). The results showed that there was a positive and significant relationship between Service Quality (X 1 ) and User Satisfaction (Y) of 0.319 and the coefficient of determination contributed 22.9%. The correlation of other variables shows that there is a positive and significant relationship between Complaint Handling (X 2 ) and User Satisfaction (Y) of 0.360 and the coefficient of determination of 22.1%. Simultaneously there is a positive relationship between Service Quality (X 1 ) and Complaint Handling (X 2 ) with User Satisfaction (Y) of 0.271 and a coefficient of determination of 32.5%.